أهمية الوقف العلمي ودوره في تعزيز التزام منظمات الأعمال بمسؤولياتها الاجتماعية -الكراسي العلمية الوقفية أنموذجا - جديدي, روضة (University of Eloued جامعة الوادي, 2017)
يعتبر الوقف العلمي ممثلا في الكراسي العلمية الوقفية إحدى الصور التي تجسد السلوك الاجتماعي المسؤول، والذي يحمل في طياته كل معاني التعاون والتكافل الاجتماعي بين منظمات الأعمال والمجتمعات التي تعمل فيها،وذلك بالمساهمة في ترقية البحث العلمي وتطويره عبر تمويل الأبحاث العلمية والتخصصات الأكاديمية في الجامعات والمعاهد التعليمية. ومن هذا المنطلق تهدف هذه الدراسة إلى إبراز أهمية الوقف العلمي ودوره في تعزيز التزام منظمات الأعمال بمسؤولياتها الاجتماعية وقد توصلنا إلى أن الوقف العلمي كان عامل أساسي في ازدهار الحضارة الإسلامية وتقدمها ، والآن هو شريك أساسي في العملية التعليمية في الدول الغربية وذلك بدافع تحقيق المسؤولية الاجتماعية بكل أبعادها ومظاهرها. Abstract: The scientific endowment (research chair) is one of the aspects that embodies the responsible social behaviorrepresenting all types of cooperation and social solidarity between business organizations and communities, by contributing to the promotion of scientific research and development through funding researches and academic specialties in universities and educational institutes. This study aims to highlight the importance of scientific endowment and its roles in strengthening the commitment of business organizations to social responsibilities.We reached that scientific endowment was a key factor in the prosperity and progress of Islamic civilization and now it is a effective partner of the educational process in western countries for the purpose of achieving social responsibility in all its aspects and dimensions.
The importance of scientific endowment and its role in sustaining the commitment of business organizations towards social responsibilities
مجلة رؤى المجلد السابع العدد 12
Keywords: الوقف ،الوقف العلمي، المسؤولية الاجتماعية، الكراسي العلمية: Endowment; scientific Endowment; social responsibility; scientific chair. (JEL) Classification : M14.